Perceptions of strategies for revitalizing industrial work experience scheme toward vocational and business education graduates’ employability in public universities, Nigeria - Ibhade Joy Ojeaga; David Nwanna Dumbiri (Jurnal Pendidikan Teknologi Kejuruan, 2023)
This paper investigated educators and students’ of vocational and business education students’ perceptions of strategies for revitalizing industrial work experience scheme in public universities in Edo State. Four research questions and one hypothesis guided the study. The study utilized the descriptive survey. A sample of 66 vocational and business educators and 178 students making a total 242. The study used stratified random sampling technique. The instrument was a 4-point scale. It was rated Strongly Agree, Agree, Disagree and Strongly Disagree and assigned weights of 4, 3, 2 and 1 respectively. Two experts in Vocational Education validated the instrument. Reliability was done with test-retest method. 20 copies of the instrument were administered on 20 business education students who are in the population but not in the sample. The first and second administrations of the instrument were done in an interval of one week interval. Analyses of the data was done with PPMC (Pearson Product Moment Correlation) Coefficient and the reliability coefficient of the instrument yielded α = .78. Data for the study was analyzed with percentage, mean, standard deviation and t-test. Findings revealed that vocational educators and students agreed that all the institution based strategies such as train the institution based supervisors on the goals of ITF, identify placement opportunities for student’s attachment and plan practical contents and real life learning experience among others are necessary for effective revitalization of SIWES.